Solidification–microprestress–microplane (SMM) theory for concrete at early age: Theory, validation and application - Di Luzio, Giovanni; Cusatis, Gianluca (International journal of solids and structures, 2013)
► A constitutive model for the mechanical behavior of concrete at early age and beyond is presented. ► The model is entitled solidification–microprestress–microplane (SMM) model. ► The SMM model amalgamates the microplane model and the solidification–microprestress theory. ► Cracking/damage behavior is modeled through an age-dependent microplane model. ► The SMM model can reproduce well the interplay of shrinkage, creep, and cracking phenomena. This paper presents a new constitutive model describing the mechanical behavior of concrete at early age and beyond. This model, entitled solidification–microprestress–microplane (SMM) model, amalgamates the microplane model and the solidification–microprestress theory and takes into account all the most significant aspects of concrete behavior, such as creep, shrinkage, thermal deformation, and cracking starting from the initial stages of curing up to several years of age. Age-dependent viscoelastic behavior under variable hygro–thermal conditions is described according to the solidification–microprestress theory. Cracking/damage behavior is modeled through an age-dependent microplane model, in which the model parameters are assumed to be dependent on an aging variable evolving with the extent of early-age chemical reactions (hydration, silica-fume reaction, etc.) and temperature. Calibration and validation of the model is performed by the numerical simulations of the age-dependent response of sealed and unsealed specimens subject to a variety of loading conditions and/or drying. Comparison with experimental data shows that the SMM model can reproduce well the interplay of shrinkage, creep, and cracking phenomena during curing and drying.